UI/UX Optimization of GOBIS Suroboyo Application with User Centered Design Approach and Short User Experience Questionnaire - Mayangsari, Mustika Kurnia; Fatihia, Wifda Muna (Politeknik Negeri Batam, 2025)
GOBIS Suroboyo is a mobile application designed to assist Suroboyo Bus passengers in accessing route information, schedules, and general bus details. Despite its potential, the application has lacked systematic user experience evaluation, resulting in usability issues that require improvement. This study aims to optimize the user interface (UI) and user experience (UX) of the GOBIS Suroboyo application using the User-Centered Design (UCD) approach. The research was conducted through four main stages: analysis of the existing application, identification of user needs, redesign of the interface, and evaluation of the resulting prototype. The usability evaluation was performed using the Short User Experience Questionnaire (UEQ-S), which assessed both hedonic and pragmatic qualities. The results showed mean scores of 1.69 for hedonic quality and 1.425 for pragmatic quality, which fall into the